Some aspects of the energy exchange in an ionizing particle track for organic solid detectors - Galunov, N.Z.; Tarasenko, O.A. (Вопросы атомной науки и техники, 2014)
This work studies the radioluminescence energy yield of organic solid scintillators. The energy that is necessary to produce a scintillation photon is calculated for different ionizing radiations. The analysis of the results is based on the study of the physical processes proceeding during the early stages of the ionizing particle energy exchange. It bases on the concept of a decisive influence of the polarization, which appears in an organic molecular medium, on the recombination of hot charge carriers that results in reduction of the radioluminescence energy yield. The possible reasons of the energy losses are also analyzed.